Perlindungan Hukum Para Pihak dalam Perjanjian Elektronik Menurut Hukum Perdata Indonesia - Hardito Nawaskoro; Luthfiyyah Amalina Husna (PT. Lembaga Penerbit Penelitian Nusantara, 2026)
Advances in information and communication technology have spurred substantial changes in legal transaction procedures in Indonesia, primarily through the utilization of electronic agreements. Agreements that were previously made in traditional paper formats are now frequently conducted digitally, raising legal concerns regarding their legality, validity, evidence, and legal protection for the involved parties, particularly consumers. Although electronic agreements are normatively recognized in the Civil Code (KUHP) and the Law on Electronic Information and Transactions, practical implementation issues persist, leading to legal uncertainty. This research employs a normative legal methodology utilizing statutory, conceptual, and comparative approaches. Data was obtained through a literature review of primary, secondary, and tertiary legal sources related to electronic agreements and civil legal protection. Qualitative descriptive analysis was conducted to investigate the legal status of electronic agreements and the legal protection available for the parties within the Indonesian legal framework. The discussion results indicate that electronic agreements possess legal validity and binding force equivalent to traditional agreements, provided they meet the criteria for a valid agreement as outlined in Article 1320 of the Civil Code and the provisions of the Information Technology Law. Legal protection in electronic agreements encompasses legal certainty, the recognition of electronic document and signature evidence, and consumer protection against detrimental standard clauses. Nevertheless, challenges remain in establishing party identification, ensuring the integrity of digital contracts, and addressing power imbalances between commercial entities and consumers. This study concludes that while electronic agreements are legally recognized under Indonesian civil law, enhancing legal protection requires strengthened regulations, consistent law enforcement, and improved legal and digital literacy among the public to ensure secure, fair, and equitable electronic transactions.